Phase space properties and chaotic transport for a particle moving in a time dependent step potential well - Da Costa, Diogo Ricardo; Caldas, Iberê L.; Leonel, Edson D. [UNESP] (Elsevier, 2014)
Some dynamical properties for an ensemble of non-interacting classical particles along chaotic orbits and transport properties over the chaotic sea for the problem of a step and time dependent potential well are considered. The dynamics of each particle is described by a two-dimensional, nonlinear and area preserving mapping for the variables energy and time. The phase space is of mixed-type and contains periodic islands, a set of invariant KAM curves and chaotic seas. The chaotic orbits are characterized by the use of Lyapunov exponents. Transport over the chaotic sea is considered and scaling exponents are obtained. A sticky region around a chain of periodic islands produces local and temporarily trapping of the dynamics and discussions of the rearrangement of the phase space are made. © 2014 Elsevier B.V. All rights reserved.
Keywords: Chaos; Chaotic transport; Phase space properties; Step potential well